Thinking like an engineer : an active learning approach /: an active learning approach. ([2015]) - Stephan, Elizabeth A; Bowman, D. R (David Richard); Park, W. J (William John); Sill, Ben L, 1945-; Ohland, Matthew W
No abstract available